Structure of Arabic Scale of Death Anxiety With Chinese College Students: A Bifactor Approach - Li, Qiuyun; Cai, Yan; Tan, Qingrong; Tu, Dongbo (Frontiers in Psychology, 2018)
ASDA is one of the most widely used measures of death anxiety (DA), although it is being increasingly applied in many research, the structures derived from different studies have been highly inconsistent. In this study, both traditional and novel (bifactor) modeling approaches were used to investigate the most optimal structure of the Arabic Scale of Death Anxiety (ASDA) on the sample of 984 Chinese college students. After a series of comparisons, the results showed that the bifactor model with a dominant general DA factor and three distinct sub-dimensions is the most optimal measurement structure (χ2(133) =703.538*; p<.001, CFI=.927, TLI=.906, RMSEA=.066 [90% CI .061-.071], and SRMR=.043). The discussion focuses on the impact of the bifactor structure for scale scoring, and some strengths and limitations of this study were also discussed in the context of these findings in the end.